Coffee and tea intake and risk of brain tumors in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort study. - Michaud, D; Gallo, V; Schlehofer, B; Tjønneland, A; Olsen, A; Overvad, K; Dahm, C; Teucher, B; Lukanova, A; Boeing, H; Schütze, M; Trichopoulou, A; et al. (2010)
BACKGROUND: In a recent US cohort study, total coffee and tea consumption was inversely associated with risk of glioma, and experimental studies showed that caffeine can slow the invasive growth of glioblastoma. OBJECTIVE: The objective was to examine the relation between coffee and tea intake and the risk of glioma and meningioma in a large European cohort study, the European Prospective Investigation into Cancer and Nutrition (EPIC). DESIGN: Data on coffee and tea intake were collected from men and women recruited into the EPIC cohort study. Over an average of 8.5 y of follow-up, 343 cases of glioma and 245 cases of meningioma were newly diagnosed in 9 countries. We used Cox proportional hazards models to examine the relation between coffee and tea and brain tumors. RESULTS: We observed no associations between coffee, tea, or combined coffee and tea consumption and risk of either type of brain tumor when using quantiles based on country-specific distributions of intake. However, a significant inverse association was observed for glioma risk among those consuming ≥100 mL coffee and tea per day compared with those consuming <100 mL/d (hazard ratio: 0.66; 95% CI: 0.44, 0.97; P = 0.03). The association was slightly stronger in men (hazard ratio: 0.59; 95% CI: 0.34, 1.01) than in women (hazard ratio: 0.74; 95% CI: 0.42, 1.31), although neither was statistically significant. CONCLUSIONS: In this large cohort study, we observed an inverse association between total coffee and tea consumption and risk of glioma that was consistent with the findings of a recent study. These findings, if further replicated in other studies, may provide new avenues of research on gliomas.